2021
DOI: 10.1037/prj0000409
|View full text |Cite
|
Sign up to set email alerts
|

Romantic relationships, sexuality, and psychotic disorders: A systematic review of recent findings.

Abstract: For individuals with a psychotic disorder, dating can present several challenges and lead many to be excluded from intimate relationships. These difficulties may stem from a number of factors, including impairments in social and sexual functioning. Although scientific interest in this topic is mounting, the last quantitative review of the literature dates back to 2003. Objectives: The aim of this systematic review was to collect, evaluate, and synthesize quantitative data from studies published in the last 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…These include use of antipsychotics (de Boer et al, 2015), self-stigma, difficulties in social cognition, social isolation and loneliness and sexual trauma (McCann et al, 2019). Findings of a recent systematic review of 43 quantitative studies are largely in line with those reported by McCann and colleagues (Cloutier et al, 2020).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…These include use of antipsychotics (de Boer et al, 2015), self-stigma, difficulties in social cognition, social isolation and loneliness and sexual trauma (McCann et al, 2019). Findings of a recent systematic review of 43 quantitative studies are largely in line with those reported by McCann and colleagues (Cloutier et al, 2020).…”
Section: Introductionsupporting
confidence: 67%
“…In other words, replication in the current era of psychiatry is required. Nevertheless, other studies using more recent data have reached similar conclusions regarding the position of sexuality and intimacy in mental health care (Cloutier et al, 2020;McCann et al, 2019). Lastly, sexuality and intimacy needs were analyzed quantitatively, but not explored qualitatively.…”
Section: Discussionmentioning
confidence: 95%
“…On the one hand, it is a part of everday normal life experiences. On the other, it is regarded as a sensitive topic and certainly a clinical assessment criterion that can create discomfort for clinicians ( 14 ) and patients ( 22 ). This is possibly why very few studies have evaluated sexuality and sexual functioning in people with mental illness, even though the evidence shows that mental illness, social impairments, and institutionalization all affect an individual's sexuality and sexual functioning ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since interpersonal relationships and intimacy play a key role in early psychosexual development, it is easy to imagine how mentalization among these patients might be crucial during these years. A recent review article has indeed underscored how dating might be extremely challenging for people with psychotic disorders, as romantic and intimate relationships are often precluded for such patients ( 14 ). From a psychodynamic point of view, a disrupted ToM might result in a compromised capacity to integrate sexual states in one's own developing identity, therefore producing high levels of distress ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since sexual dysfunction deeply weighs on QOL ( 19 ), it is easy to understand how neglecting sexual health might represent a relevant barrier in mental health promotion and a dangerous risk factor among young people with a clinical high risk of developing full-blown schizophrenia. In keeping more closely with this issue, two recent review articles discuss how important it is to better assess intimacy and sexuality among young people with FEP and psychotic disorders in general ( 14 , 20 ). However, to date, a comprehensive review of sexual dysfunction among patients with a clinical high risk of developing psychosis is still missing.…”
Section: Introductionmentioning
confidence: 99%